On “Huxleys Evolution and Ethics in Sociobiological Perspective” by George C. Williams - Burhoe, Ralph W. (Zygon, 1988)
Abstract. I concur with Williams that improving human ethics requires full consideration of the biogenetic facts; but I argue that the understanding of biogenetic facts, and of ethics also, can be improved by a fuller view of nature's mechanism for selecting what is fit, a view recently generated by physical scientists. For me ethics necessarily must fit the evolved genotype, but ethics does not emerge until the rise of cultural evolution, where nature selects a culturetype symbiotic with the genotype. I outline my integrated dynamics of the relation of culturetypes to genotypes and to the laws governing physical systems. The biologist's finding that a living organism is of transient significance compared with its lines of heritage and their consequences, I argue, is constructively important for ethical and theological understanding.